Study the Elevation of Fibrinogen level in Plasma Patients with Diabetes Mellitus Type 2 in Babylon Governorate - Khawla A. Shemran (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: The incidence of diabetes mellitus type 1 and type 2 has increased dramatically worldwide in thepast 20 years. Type 2 diabetes is probable to increase further in the future owing to the increase in obesityand the lack of exercise. This may rise the danger of unindustrialized cardiovascular illness in patientswith type 2 DM. It may be because fibrinogen has an important role in the increased risk of cardiovasculardisease. The aims of current study to find out the level of fibrinogen and its relationship to the level of bloodglucose in patients with type 2 DM. Methods: The study contain 50 patient with diabetes mellitus type 2 aspatient group and 50 adult apparently healthy as control group. All plasma samples were collected from allsubjects. The age for both groups concerning (43-75) years. The collected data include measures, plasmafibrinogen and HbA1c. Results: The present study revealed a significant increase in plasma fibrinogen,HbA1c concentration in patients compared with control group (p<0.01). Conclusion: The results of thisstudy reveal a significant increase in fibrinogen level in patients with diabetes mellitus type 2 withoutcardiovascular disease.